The Role of Sharia Economy in Building Sustainable MSMEs in Indonesia - Rinaldi, Afdhol; Nurcahaya (JAWI : Journal of Ahkam Wa Iqtishad, 2025)
MSMEs play an important role in driving national economic growth, creating jobs, and improving community welfare. However, MSMEs still face various challenges such as access to capital and business guidance. The Sharia economy has emerged as a solution for empowering MSMEs through the principles of justice, transparency, and adherence to Sharia-based values. This article discusses how the Sharia economy can support MSME empowerment through various instruments such as Islamic financial institutions, zakat, infaq, alms, and productive waqf. The research method used was a literature review using a descriptive-qualitative approach. The results of the study indicate that the optimal application of Sharia economic principles can make MSMEs more competitive and contribute to equitable welfare distribution among Indonesian people.